A Diet Rich in Olive Oil Phenolics Reduces Oxidative Stress in the Heart of SAMP8 Mice by Induction of Nrf2-Dependent Gene Expression - Bayram, Banu; Ozcelik, Beraat; Grimm, Stefanie; Roeder, Thomas; Schrader, Charlotte; Ernst, Insa M. A.; Wagner, Anika E.; Grune, Tilman; Frank, Jan; Rimbach, Gerald (SAGE Publications, 2012)
A Mediterranean diet rich in olive oil has been associated with health benefits in humans. It is unclear if and to what extent olive oil phenolics may mediate these health benefits. In this study, we fed senescence-accelerated mouse-prone 8 (SAMP8, n =11 per group) semisynthetic diets with 10% olive oil containing either high (HP) or low amounts of olive oil phenolics (LP) for 4.5 months. Mice consuming the HP diet had significantly lower concentrations of the oxidative damage markers thiobarbituric acid–reactive substances and protein carbonyls in the heart, whereas proteasomal activity was similar in both groups. Nrf2-dependent gene expression may be impaired during the aging process. Therefore, we measured Nrf2 and its target genes glutathione- S -transferase (GST), γ-glutamyl cysteine synthetase (γ-GCS), nicotinamide adenine dinucleotide phosphate [NAD(P)H]:quinone oxidoreductase (NQO1), and paraoxonase-2 (PON2) in the hearts of these mice. Nrf2 as well as GST, γ-GCS, NQO1, and PON2 mRNA levels were significantly higher in heart tissue of the HP as compared to the LP group. The HP-fed mice had significantly higher PON1 activity in serum compared to those receiving the LP diet. Furthermore, HP feeding increased relative SIRT1 mRNA levels. Additional mechanistic cell culture experiments were performed, and they suggest that the olive oil phenolic hydroxytyrosol present in the HP oil may be responsible for the induction of Nrf2-dependent gene expression and the increase in PON activity. In conclusion, a diet rich in olive oil phenolics may prevent oxidative stress in the heart of SAMP8 mice by modulating Nrf2-dependent gene expression.
Keywords: Aging; Phenol; NF-E2-Related Factor 2; Iron; Myocardium; Oxidants; Animal Feed; Antioxidants; Mice; Oxidative Stress; Gene Expression Regulation; Spectrophotometry; Animals; Plant Oils; Female; Lipid Peroxidation; Olive Oil; Cellular Senescence